Cultural perceptions of child abuse in terms of parents’ perspective: a qualitative study in Bandung-Indonesia - Reizkiana Feva Kosmah Dewi; Viramitha Kusnandi Rusmil; Sri Endah Rahayuningsih; Kuswandewi Mutyara; Nita Arisanti; Nanan Sekarwana; Meita Dhamayanti (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Child abuse (CA) is a serious problem and difficult to detect. According to World Health Organization, CA is responsible for 950,000 deaths of children. Many various cultural norms may affect CA. This research aims to determine the cultural perceptions of child abuse in terms of parents in Indonesia. A qualitative study using focus group discussions (FGDs) was conducted with 31 parents who were selected purposively. The FGDs centered on the CA definition, classification, frequency, level of CA (mild, moderate, and severe), and the difference between violence and discipline. The FGDs were divided into three groups based on level of education completeed: elementary and junior high school, senior high school, and bachelor’s degree. The process of the FGDs was recorded, transcribed, and analyzed using manifest qualitative content analysis. This study was conducted from December 2018 to April 2019 in Pamekaran, Soreang Bandung. Every culture in Indonesia perceived that CA is a form of parents’ emotion that could injure children physically and mentally. Indonesian cultures were not familiar with neglect and exploitation. Participants’ opinions regarding level of violence can be categorized as severe if leaving wounds, and needing to be hospitalized. The parents assumed there was CA if it occurred more than twice and/or leaving marks. The discipline purpose is not to mistreat, but for protecting their children’s life, building characters, and educating the children. In conclusion, a cultural perception of parents about CA is a form of parents’ emotion which leads to injury of children physically and mentally.